Hypolipidemic Effect Of Black Cumin (Nigella Sativa) Oil On Adult Layer Birds (Applied Biological Research, 2015)
The present study was aimed to assess the effect of black cumin (Nigella  sativa) oil on serum lipid profile and β-hydroxy, β-methylglutaryl  coenzyme-A reductase (HMG CoA reductase) gene expression in adult  layer birds. Thirty six weeks old White Leg Horn (WLH) layer birds  were randomly divided into five groups consisting of 6 birds each. Their  diets were supplemented with 0 (control), 1.0, 2.0, 3.0 and 4.0 g black  cumin oil kg-1 feed, respectively. Blood samples were collected on day 0,  14, 28, 42 and 56 and study further continued for one more month  without supplementing the diet with herbal preparations in order to  observe the withdrawal effect. Gene expression studies of HMG CoA  reductase were carried out in the liver tissue of the birds by real time  quantitative PCR analysis on day 56. Serum total lipids, cholesterol, tri glycerides, HDL, LDL and VLDL-cholesterol varied highly significantly  (p 3> 2> 1> 0 g  cumin oil kg-1 feed. The study revealed that the supplementation of  black cumin oil @ 4 g kg-1 feed is most effective in reducing serum lipid  profile and HMG CoA reductase gene expression after 56 days. These  effects gradually reduced with time after the withdrawal of oil.
Keywords: Black cumin oil; gene expressions; HMG CoA reductase; lipid profile; White Leg Horn layer birds